2003
DOI: 10.2337/diabetes.52.7.1627
|View full text |Cite
|
Sign up to set email alerts
|

Contraction-Induced Fatty Acid Translocase/CD36 Translocation in Rat Cardiac Myocytes Is Mediated Through AMP-Activated Protein Kinase Signaling

Abstract: Contraction of rat cardiac myocytes induces translocation of fatty acid translocase (FAT)/CD36 and GLUT4 from intracellular stores to the sarcolemma, leading to enhanced rates of long-chain fatty acid (FA) and glucose uptake, respectively. Because intracellular AMP/ ATP is elevated in contracting cardiac myocytes, we investigated whether activation of AMP-activated protein kinase (AMP kinase) is involved in contractioninducible FAT/CD36 translocation. The cell-permeable adenosine analog 5-aminoimidazole-4-carb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

23
264
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 264 publications
(302 citation statements)
references
References 46 publications
(47 reference statements)
23
264
0
1
Order By: Relevance
“…Previously we established that there are two signaling pathways linked to the translocation of FAT/CD36 from an intracellular compartment to the sarcolemma: insulininduced PI 3-kinaseϪdependent signaling (13)(14)(15) and contraction-induced AMPK-dependent signaling (18). Accordingly, in the present study, we found that in vitro insulin and oligomycin were effective in inducing FAT/ CD36 translocation and stimulating LCFA uptake in cardiac myocytes from lean rats.…”
Section: Discussionsupporting
confidence: 57%
See 2 more Smart Citations
“…Previously we established that there are two signaling pathways linked to the translocation of FAT/CD36 from an intracellular compartment to the sarcolemma: insulininduced PI 3-kinaseϪdependent signaling (13)(14)(15) and contraction-induced AMPK-dependent signaling (18). Accordingly, in the present study, we found that in vitro insulin and oligomycin were effective in inducing FAT/ CD36 translocation and stimulating LCFA uptake in cardiac myocytes from lean rats.…”
Section: Discussionsupporting
confidence: 57%
“…The effect of cellular contractions on myocardial LCFA utilization was studied by means of oligomycin, a compound that inhibits F 0 /F 1 ATPase activity at relatively low concentrations. Oligomycin, at an optimal concentration (30 mol/l), increased the AMP kinase activity in cardiac myocytes by elevating the intracellular AMP/ATP ratio to approximately the same extent as that observed with cellular contractions (18). To investigate the role of FAT/CD36 in myocardial LCFA uptake and utilization in lean and obese Zucker rats, cardiac myocytes were treated with sulfo-Nsuccinimidyloleate (SSO), which inactivates FAT/CD36 by covalently binding to its LCFA binding site (24,25).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1A). Oligomycin, an inhibitor of mitochondrial F 1 F 0 -ATPase, has been previously shown to stimulate AMPK and PKD activation in a similar manner as does contraction (3,7) and was used in these experiments as stimulus to verify whether the down-regulation of synthesis of both kinases would also reduce their activation. Silencing of PKD1 resulted in a complete loss of oligomycin-induced PKD1-Ser 916 phosphorylation, and silencing of AMPK led to a complete loss of oligomycin-induced AMPK-Thr 172 phosphorylation.…”
Section: Involvement Of Pkd1 and Ampk In Contraction-inducedmentioning
confidence: 99%
“…Alterations in contraction are an important denominator of cardiac substrate utilization. Increased contraction enhances the demands for glucose and LCFA, and accordingly, GLUT4 and CD36 have been found to translocate to the sarcolemma under this condition (1,3).…”
mentioning
confidence: 99%